DETERMINANTS OF ENTREPRENEUR’S PERFORMANCE IN MSMEs IN EAST JAVA - Mustika, Hindah; Handayani, Nur; Amanah, Lailatul; Abbas, Ansar; Ahmad, Muhammad Ali (Fakultas Ekonomi dan Bisnis, UNTAN, 2025)
Entrepreneur's performance is the result of work that has been finished by someone and this will have a positive impact on the sustainability of an organization. The purpose of this research aims to test and analyze the influence attitude to entrepreneur, subjective norm, perceived behavior control, intention to entrepreneur, spirituality on entrepreneur's performance in maintaining the survival of MSMEs in East Java. Methodology a quantitative survey was carried out and the data sample of 251 classic product business owners in East Java was collected using quota sampling technique. Partial least squares-based structural equation modeling (PLS-SEM) was employed to test the hypothesized relationships. Results that for the direct influence test of the 5 hypotheses there were two significant influence tests accepted and an indirect influence test where there were 4 hypotheses, of which one significant hypothesis was accepted. The results of this research have implications for owners of MSMEs, especially in East Java, to understand that it is necessary to think about intrinsic and extrinsic motivation so that it will become a strategy in maintaining survival. JEL: L66, L67, L68.